2013
DOI: 10.1007/s10067-013-2172-z
|View full text |Cite
|
Sign up to set email alerts
|

Low occurrence of digital ulcers in scleroderma patients treated with bosentan for pulmonary arterial hypertension: a retrospective case–control study

Abstract: Digital ulcers (DU) are one of the most common and debilitating manifestations of vasculopathy in systemic sclerosis (SSc). Their prevention is important in order to improve patients' outcome and as a result of the economic impact they have on society. Randomised controlled studies have demonstrated that bosentan, an endothelin receptor antagonist, reduces the appearance of new DU. The aim of this retrospective study was to evaluate the occurrence of DU in a group of patients receiving long-term bosentan treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Despite having side effects such as increases in liver transaminase content, headache, peripheral oedema, dizziness, nasal congestion and nausea, bosentan therapy is generally regarded as beneficial (Montani et al 2013 ; Motte et al 2006 ). Bosentan also has been found to exert a positive therapeutic influence on the treatment of systemic sclerosis (scleroderma) and other disorders (Cozzi et al 2013 ) (Table 3 ).…”
Section: Bosentanmentioning
confidence: 99%
“…Despite having side effects such as increases in liver transaminase content, headache, peripheral oedema, dizziness, nasal congestion and nausea, bosentan therapy is generally regarded as beneficial (Montani et al 2013 ; Motte et al 2006 ). Bosentan also has been found to exert a positive therapeutic influence on the treatment of systemic sclerosis (scleroderma) and other disorders (Cozzi et al 2013 ) (Table 3 ).…”
Section: Bosentanmentioning
confidence: 99%
“…These findings are in agreement with those reported in a long-term observational study showing the low occurrence of digital ulcers in patients with systemic sclerosis receiving bosentan for PAH. 9 Increased ET-1 activity inhibits nitric oxide synthesis, which has been found to be impaired in patients with systemic sclerosis. 10 Bosentan improves exercise-induced and flow-mediated pulmonary vasodilatation and thus restores endothelial function by increasing nitric oxide production.…”
Section: Discussionmentioning
confidence: 99%
“…First-line treatment and prevention strategy of chronic ulcers are calcium channel blockers [48] with addition of PDE5i for second-line treatment [24•]. ERAs have been shown to help in prevention of new digital ulcers [71], but most studies do not demonstrate efficacy in healing ulcers [49]; thus, they are usually considered third-line therapy. In active ischemia, there is not a consensus on first-line therapy, but IV prostaglandins should be considered for treatment as randomized controlled trials have shown efficacy in healing digital ulcers [51,52].…”
Section: Digital Vasculopathymentioning
confidence: 99%